All India Grievance Redressal App (Journal of Information Technology and Digital World, 2020)
Citizens of the India face civic problems in their day-to-day lives. They resort to the one of many ways provided by the government to file their complaints. The grievance registration systems have evolved in many ways with the advancement in technologies to simplify the task. This paper presents the architecture of a Grievance redresser Application where the civilians can address any kind of complain which they are facing. The main focus of the project is about the pothole related complains. One of the most difficult task for the government officials to estimate the total time and material required to fill the pothole of widely spaced roads, this is one of the major problem faced by government authorities which leads to delaying in repairing the pothole and increased the cost to fill a particular pothole. This Application will give easy access to people to put their complaints towards the government.
Keywords: Potholes; Complaints; Android; GPS location; Geocoding